Social Interaction Growing Social Concern among Children RA Az-Zahra in Pidie Jaya District - Elia Nora; Wahyu Khafidah; Rizqiannisa Rizqiannisa (Universitas Serambi Mekkah, 2022)
The character of an individual is formed since he was small due to genetic influences and the surrounding environment. The process of character formation, whether consciously or not, will influence the way the individual views himself and his environment and will be reflected in his daily behavior. Along with the times, accompanied by the development of information technology, it has resulted in a shift in values and a lot of deviant behavior that occurs in children, so that parents and educational institutions and the community need to pay serious attention to building children's character education. This research is a descriptive study using a qualitative approach. A qualitative approach can be interpreted as an approach that produces data, writing, and observed behavior from people. It is found that Social care needs to be developed so that children do not have negative traits, such as arrogance, indifference, individualism, indifference to social problems, picky friends and the fading of the culture of mutual cooperation. Social care is an attitude and action that always wants to provide assistance to other people and communities in need. Keywords: Social Interaction, Growing Social, Children.